ANALYSIS OF COMPLIANCE WITH THE USE OF PPE DURING THE COVID-19 PANDEMIC AT PUSKESMAS DUMBAYABULAN YEAR 2022 - Djakaria, Hamawiyah Netrisya (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
In the Covid-19 case in Indonesia itself, the government has issued a status disaster emergency starting on February 29, 2020, related to this virus pandemic. Personal Protective Equipment (PPE) is used to protect oneself or the body against the dangers of work accidents and the risk of contracting the virus, especially related to biological hazards. This study aims to analyze the factors related to health workers' compliance with the use of PPE during the COVID-19 pandemic in the Dumbaya Bulan Health Center Work Area. This study uses a Chi-Square design. The population is 38 people, and the research sample is presented. Data were collected by data analysis using chi-square. Results: the study showed that the variables, namely knowledge (p=0.007) and information and research (p=0.010), had a significant relationship with health workers' compliance in using PPE in Dumbayabulan Health Center. Meanwhile, perceptions of risk (p=1,000), barriers (p=0,252), workload (p=0,160), safety climate (p=0,313) and availability of facilities and facilities (p=0,517) did not have a significant relationship with compliance. health workers in the use of PPE at Dumbayabulan Health Center. Increasing vigilance in infection prevention and control in treating patients using PPE is necessary.